Dispositif de médiation numérique des savoirs professionnels en situation de classe : - Laurent Fauré; Cécile Gardiès; Jean-François Marcel (Centre National d'Enseignement à Distance, 2015)
Teaching practices are discussed here in relation to the issue of information taken in complex teaching situations, as defined by Doyle (1986). We develop a theoretical approach based on three points: the model of teacher's thought during classroom interaction, the concepts of experienced teachers and teacher novices and professional knowledge. We then present an experimental protocol for collecting data involving a number of professional knowledge mediation between an experienced teacher and novice teacher in situation of teaching and learning in science and technology in agricultural equipment agricultural education. The results show that mediation in situation by experienced teacher, delivering information from its expertise to novice teacher, helps to increase his perception of indices, which allows us, because of the modified action, to postulate a contribution to the construction of new knowledge.